2019
DOI: 10.1038/s41467-019-11241-6
|View full text |Cite
|
Sign up to set email alerts
|

RNA is a critical element for the sizing and the composition of phase-separated RNA–protein condensates

Abstract: Liquid–liquid phase separation is thought to be a key organizing principle in eukaryotic cells to generate highly concentrated dynamic assemblies, such as the RNP granules. Numerous in vitro approaches have validated this model, yet a missing aspect is to take into consideration the complex molecular mixture and promiscuous interactions found in vivo. Here we report the versatile scaffold ArtiG to generate concentration-dependent RNA–protein condensates within living cells, as a bottom-up approach to study the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(140 citation statements)
references
References 74 publications
2
137
0
1
Order By: Relevance
“…Thus, for assemblies like SGs, which contain a high local concentration of RNA molecules, RNA‐RNA interactions and RNA structure seem to be general features of importance for their formation. Detailed information about the roles of RNA in forming SGs and other RNP granules can be found in recent reviews (Garcia‐Jove Navarro et al, 2019; Van Treeck & Parker, 2018).…”
Section: Stress Granule Formation and Regulationmentioning
confidence: 99%
“…Thus, for assemblies like SGs, which contain a high local concentration of RNA molecules, RNA‐RNA interactions and RNA structure seem to be general features of importance for their formation. Detailed information about the roles of RNA in forming SGs and other RNP granules can be found in recent reviews (Garcia‐Jove Navarro et al, 2019; Van Treeck & Parker, 2018).…”
Section: Stress Granule Formation and Regulationmentioning
confidence: 99%
“…While BMCs assemble by thermodynamic-mediated liquid-liquid phase separation, the liquid BMCs are known to transform into reversible amyloid fibers or insoluble aggregates [70]. While the details of BMC biology is still evolving, it has been shown that RNA and proteins with intrinsically disordered regions are key factors that influence the intracellular composition, size, and morphology of BMCs [71,72]. Unlike BMCs, EVs contain at least one membrane.…”
Section: Potential Role Of Extracellular Structures-biomolecular Condmentioning
confidence: 99%
“…Our understanding of the biophysical and biochemical principles that govern granule diversity, assembly and disassembly has recently benefited from new conceptual frameworks. LLPS has emerged as an attractive model to explain the observed properties of membrane-less organelles, including RNP granules [11,48,[80][81][82][83]. The earliest example of maternal RNP structures shown to exhibit liquid-like behaviour were induced 'bodies' found in the Drosophila oocyte nucleus.…”
Section: Examples Of Phase Separation During Early Drosophila Developmentioning
confidence: 99%
“…RNA storage and translational control is likely a major function of RNP granules in oogenesis as they form in response to high levels of untranslated mRNAs and disperse at a time when many mRNAs are translated. While proteins are typically considered to be the key scaffolds for granule assembly, more recently RNA has also been shown to both phase separate and drive the assembly of RNP condensates [80,83,107,108].…”
Section: The Role Of Rnamentioning
confidence: 99%
See 1 more Smart Citation